Phytocoenofund’s Rarities in Fruticose, Fruticulose and Herbaceous Vegetation of Southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
An analysis of contemporary state of phytocoenotic diversity of south en Ukraine and principal anthropogenic factors that determine its degradation is provided. In spite of extensive human impact, the region in is characterized by high floristic (more than 2000 species of vascular plants) and coenotic (more than 280 associations) diversity. It is stressed that because of mezophytization, the degradation of steppe communities takes place in reserved and neglected areas. To conserve steppe vegetation it is suggested to use a model of low-intensive farm industry. An overview of the problems of settins the regional econet and the second edition of the Green Data Book of Ukraine is considered. A list of rare, endangered and vulnerable fruticose, fruticulose and herbaceous plain communities in the rank of association is proposed of Southern Ukraine. A short sozological characteristic for each of them is given.
Keywords: rare phytocoenotic fund, fruticose, fruticulose, herbaceous vegetation, the Green Data Book of Ukraine, conservation.